The impact of HIV infection on spectrum of extrapulmonary tuberculosis in Siberia and Far East - E. V. Kulchavenya (Žurnal Infektologii, 2018)
Introduction. Human immunodeficiency virus (HIV) infection is a risk factor for tuberculosis (TB), increasing the likelihood of its development in 20–37 times. The purpose of the study was to evaluate an influence of HIV infection on a spectrum of extrapulmonary tuberculosis (EPTB). Material and methods. Statistical reports of dispensaries on tuberculosis in Siberia and Far East were analyzed for 2016–2017 years. Of total 1227 patients with isolated EPTB (without pulmonary TB) who have the status of HIV infection were enrolled in the study. пациентов с изолированными формами ВЛТ, у которых определен статус ВИЧинфицирования. Results. In the overall spectrum of the incidence of EPTB in Siberia and the Far East, estimated independently from HIV infection, the leading form with a large predominance was the bone and joints TB (41,0%). The second-third place was divided by urogenital tuberculosis and tuberculosis of the central nervous system (19,4% and 18,7% respectively). The spectrum of the incidence of EPTB changed dramatically depending on HIV infection. If in HIV-infected patients most common form was TB of the central nervous system (43.8%), followed by the second – the bone and joints TB (34.5%), and TB of peripheral lymph node TB (11.7%). The proportion of urogenital tuberculosis in HIV-infected was negligible (1.9%). In the analyzed period, significant changes in the proportions of extrapulmonary tuberculosis localization in both HIV-infected and immunocompetent patients were not found. Conclusion. HIV infection dramatically changes the spectrum of the incidence of EPTB. We recommend making changes in the system of recording patients with EPTB, allocating HIV-infected to a separate group.